2015
DOI: 10.4137/bmi.s30559
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Three-Gene Signature Improves Prediction of Relapse-Free Survival in Estrogen Receptor-Positive and Node-Positive Breast Tumors

Abstract: The objective of the present study was to validate prognostic gene signature for estrogen receptor alpha-positive (ER03B1+) and lymph node (+) breast cancer for improved selection of patients for adjuvant therapy. In our previous study, we identified a group of seven genes (GATA3, NTN4, SLC7A8, ENPP1, MLPH, LAMB2, and PLAT) that show elevated messenger RNA (mRNA) expression levels in ERα (+) breast cancer patient samples. The prognostic values of these genes were evaluated using gene expression data from three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Meanwhile, three studies that focused on GATA3 mRNA expression or GATA3 mutation by PCR or RT-PCR were excluded from this meta-analysis [2931]. There is no doubt that comparing IHC-based protein expression with microarray-based gene-expression levels can lead to quite distinct conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, three studies that focused on GATA3 mRNA expression or GATA3 mutation by PCR or RT-PCR were excluded from this meta-analysis [2931]. There is no doubt that comparing IHC-based protein expression with microarray-based gene-expression levels can lead to quite distinct conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Even though a systematic biological interpretation of the signatures identified is beyond the scope of this work, to ascertain the reliability of our results we compared them with published data. The top features in the BRCA-ER rSNFi signature include multiple genes known to be associated with breast carcinoma progression and outcome such as AGR3, B3GNT and MLPH (29,30,31). In addition we find the estrogen receptor gene (ESR1 from the gene and ER-alpha from the prot layer) and the transcription factor GATA3 (from both gene and prot layers) (32).…”
Section: Resultsmentioning
confidence: 92%
“…Data from Oncomine revealed a significant upregulation of SLC7A8 in several cancers, including breast, colorectal, head and neck, leukaemia, lymphoma, and melanoma [35]. However, this only has been validated at the mRNA level in a subset of breast tumours [15] and melanoma cell lines, which showed however more than five times increase in SLC7A5 expression compared to SLC7A8 [36]. Herein, we used large BC cohorts to reveal the significant associations between the high SLC7A8 expression, at mRNA and protein levels, and good prognostic clinicopathological parameters, including small tumour size, low tumour grade, and good NPI.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited information whether SLC7A8 plays an equal role in BC. Previous studies showed that SLC7A8 is upregulated in ER+BC and it is controlled by oestrogen [4,15]. Luo et al also identified SLC7A8 as a novel progesterone target gene in uterine leiomyoma cells [16].…”
Section: Introductionmentioning
confidence: 98%